Ø±Ø¦Ø§Ø³Ø© Ø§Ù„Ù…Ø¯Ø±Ø³Ø© ÙÙŠ Ø¬Ø¹Ù„ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø³Ù‚Ø§ÙØ© Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙØ§Ù„Ø§ÙÙ‰ Ù†ÙˆØ³Ù†ØªØ±Ù‰ Ø³Ù„Ø§Ø¨Ù†Ø¬ Ù„ÙˆÙ…Ø¨ÙˆÙƒ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© - Ali Fathurrahman; Baiq Raudatussolihah (Lughatu Ad-dhat, 2023)
The purpose of this study is to find out how school leadership in cultivating Arabic, the relationship between school leadership and other schools in cultivating Arabic, and what results from school leadership in cultivating Arabic. This research includes a qualitative descriptive approach. Data collection methods used are observation methods, interview methods, and documentation methods. This observation method is used to obtain information by observing activities or circumstances that occur when school leadership cultivates Arabic. The interview method is used to obtain data or information related to school leadership in cultivating Arabic. While the documentation method is used to obtain data or information related to the profile of Madrasa Aliyah Palapa Nusantara Selebung East Lombok. From the results of research conducted by researchers at Madrasah Aliyah Palapa Nusantara, the researchers found about school leadership in cultivating Arabic, the relationship between school leadership and other schools, and what results from school leadership in cultivating Arabic.